Revised Staff Statement on Principles Underlying the Guidelines on Conditionality and Operational Guidance Note on the 2002 Conditionality Guidelines. (Policy Papers; Policy Paper ;, 2006)
Adoption of new guidelines for conditionality has been motivated by an increasing recognition of the importance of several interrelated principles for successful design and implementation of Fund-supported programs. Chief among these are national ownership of reform programs, parsimony in the application of program-related conditions, tailoring of programs to the member's circumstances, effective coordination with other multilateral institutions, and clarity in the specification of conditions. The operational issues covered in the note are grouped into three areas: (i) the process of negotiation and program design; (ii) the design of conditionality; and (iii) the presentation of conditionality in Board papers for the use of Fund resources. In some cases, implementing the guidelines involves the development of new practices. In other cases, new practices had already been adopted in selected cases, which should become routine.